Determination of insecticides malathion and lambda-cyhalothrin residues in zucchini by gas chromatography - Hayam M. Lofty; Abd El-Aziz A.; Hany H. Monir (Faculty of Pharmacy, Cairo University, 2013)
A sensitive gas chromatographic method has been developed for the determination of malathion and lambda-cyhalothrin (λ-cyhalothrin) insecticide residues in zucchini. The developed method consists of extraction with acetone, purification and partitioning with methylene chloride, column chromatographic clean-up, and finally capillary gas chromatographic determination of the insecticides. The recoveries of method were greater than 90% and limit of determination was 0.001 ppm for both insecticides. The method was applied to determine residues and the rate of disappearance of malathion and λ-cyhalothrin from fruits of zucchini (open field treatment, 50 cc of Malason/Cormandel 57% EC (emulsifiable concentrate) for 100 L of water, 20 cc of LAMBDA SUPER FOG 5% liquid for 100 L of water). The insecticide incorporated into the plants decreased rapidly with a half-life time around 0.77 day (18.5h) for malathion and 4 days for λ-cyhalothrin. It is not recommended to use zucchini before 12 h of malathion application. For λ-cyhalothrin, the preharvest interval is 5 days. Four market samples were chosen from different regions from A.R.E. and all of them showed no residues of malathion or λ-cyhalothrin.